Pipeline shield with single antiplatelet therapy in aneurysmal subarachnoid haemorrhage: multicentre experience. (14th December 2018) - Manning, Nathan W; Cheung, Andrew; Phillips, Timothy J; Wenderoth, Jason D
Abstract : Background: The Pipeline Embolisation Device with Shield technology (PED-Shield) is suggested to have reduced thrombogenicity. This reduced thrombogenicity may make it possible to use safely in the acute treatment of aneurysmal subarachnoid haemorrhage (aSAH) on single antiplatelet therapy (SAPT). Objective: To evaluate the safety and efficacy of the off-label use of PED-Shield with SAPT for the acute treatment of aSAH. Methods: Patients who underwent acute treatment of ruptured intracranial aneurysms with the PED-Shield with SAPT were retrospectively identified from prospectively maintained databases at three Australian neurointerventional centres. Patient demographics, aneurysm characteristics, clinical and imaging outcomes were reviewed. Results: Fourteen patients were identified (12 women), median age 64 (IQR 21.5) years. Aneurysm morphology was saccular in seven, fusiform in five, and blister in two. Aneurysms arose from the anterior circulation in eight patients (57.1%). Six (42.9%) patients were poor grade (World Federation of Neurological Societies grade ≥IV) SAH. Median time to treatment was 1 (IQR 0.5) day. Complete or near complete aneurysm occlusion (Raymond-Roy <3) was achieved in 12 (85.7%) patients at the end of early-acute follow-up (median day 7 after SAH). Permanent, treatment-related morbidity occurred in one (7.1%) patient and one (7.1%) treatment-related death occurred. The use of a postoperative heparin infusion (n=5) was associated with a higher rate of all complications (80.0% vs 11.1%, p=0.023) and symptomatic complications (60% vs 0.0%, p=0.028). No symptomatic ischaemic or haemorrhagic complications were observed in the patients who did not receive a post-operative heparin infusion. Nine (64.3%) patients were functionally independent on discharge from the treatment centre. Conclusion: The PED-Shield may be safe to use in the acute treatment of ruptured intracranial aneurysms with SAPT. Further investigation with a formal treatment registry is needed.